Efektifitas Bimbingan Kelompok Menggunakan Teknik Problem Solving Untuk Meningkatkan Kemampuan Komunikasi Interpersonal Pada Anggota Organisasi Persaudaraan Setia Hati Terate (PSHT) Gabus Kabupaten Grobogan - Sholeh Mujiyono; Heri Saptadi Ismanto; G. Rohastono Ajie (PT. ALHAFI BERKAH INDONESIA, 2023)
Communication between humans uses links in the form of symbols in the form of spoken language, written language, body language and others, so that messages are easily understood and comprehended by the recipient of the message. The aim of this research is to determine the effectiveness of group guidance using the Problem Solving technique in improving communication skills among members of the loyal heart terate brotherhood organization (PSHT) Gabus, Grobogan Regency. The research design used in this research is Pre-Experimental with a One Group Pretest-Posttest Design model. Data collection technique for distributing questionnaires with Likert scale assessments. The results of this research can be concluded that there has been an increase in interpersonal communication among PSHT Gabus members by using problem solving techniques. This problem solving technique has many variations of methods that can be used to solve a person's problems. With this method, PSHT members are able to solve problems well and also improve interpersonal communication between members.